Answer:
A basis is {v1,v4}
v2 = 3 v1 -11/3 v4
v3 = 1/3 v1 + 10/9 v4
v5 = -1/3 v4
Step-by-step explanation:
Lets triangulate the matrix that has the elements v1, v2, v3, v4 and v5 as their rows
[tex]\left[\begin{array}{ccc}-2&-7&2\\5&1&-5\\-4&-9&4\\-3&-6&3\\1&2&-1 \end{array}\right][/tex]
Lets divide each row by its first element, which is possible because it is different than 0
[tex]\left[\begin{array}{ccc}1&3.5&-1\\1&0.2&-1\\1&2.25&-1\\1&2&-1\\1&2&-1 \end{array}\right][/tex]
Thus v5 = v4 / -3 = -1/3 * v4. We can take it out. Also, we will take each row except the first one and substract the value of the first row from them, obtaining
[tex]\left[\begin{array}{ccc}1&3.5&-1\\0&3.3&0\\0&1.25&0\\0&1.5&0\end{array}\right][/tex]
Note that now, from the second row onwards, each row is a multiple of the other. So we can remove every row except 2 of them, for example the first one and the fourth one
We can form a base of the subspace of R³ spanned by v1,v2,v3,v4,v5 with {v1,v4}. Also, we have
v5 = -1/3*v4
(v1/-2-v3/-4)*1.5 = (v1/-2-v4/-3)*1.25, hence
0.25v1/-2 + 1.25 v4/-3 = 1.5 v3/-4
Thus
v3 = -8/3 *0.25 v1/-2 - 8/3*1.25 v4/-3 = 1/3 v1 + 10/9 v4
In a similar way,
(v1/-2-v2/5)*1.5 = (v1/-2-v4/-3)*3.3
Thus
v2 = 10/3 * (-1.8v1/-2 + 3.3v4/-3) = 3 v1 -11/3 v4